Training Of Lay Basic Life Support To Persit Mother In Denkesyah 02.04.02 Jambi - Suryadi Imran; Erwinsyah , (Stikes Syedza Saintika Padang, 2020)
Background: Regional Health Detachment 02.04.02 Jambi is a unit of the Army Health Unit under the Health of Military Region II / Sriwijaya which has a territorial health area in Jambi Province. Its characteristics are the mother wife of the Denkesyah army 02.04.02 Jambi is a very heterogeneous military community group, consisting of various tribes and races originating from all over Indonesia, the main activity of the Denkesyah 02.04.02 is to provide services and health insurance for the entire army and the army and family in the health field. its main task is to provide health support in every activity organized by the Korem in Jambi Province. with a high level of activity and can sometimes experience emergency situations in their families, so there is a need for understanding and knowledge of the handling and first aid of the emergency emergency cases, such as emergency cases can be in the form of household trauma cases such as poisoning and household accidents. The results of the survey found that ± 80% of mothers did not have knowledge about handling first aid in emergency cases, and about 60% of mothers did not know and understand handling emergency cases with the basic life support (BHD) method. Method: Training analysis model using two stages, pre-test and post-test, to find out the level of knowledge, attitudes and psychomotor of the trainees as many as 20 mothers Persit Denkesyah 02.04.02 Jambi. Research Results: There is Description of an increase in knowledge, attitudes and psychomotor after attending this training Jambi. Conclusion: The ability of a mother with the skills of a mother is influenced by the aspects of knowledge, attitudes and psychomotor that are structured in providing basic life support to emergency cases in the household. Keywords: Knowledge, attitude and psychomotor aspects, in providing basic life support